PP.42.07: FOKI AND BSMI VITAMIN D RECEPTOR GENE POLYMORPHISMS. (June 2015) - Guarino, L.; Geraci, G.; Arsena, R.; Vaccaro, F.; Guarneri, M.; Scazzone, C.; Mulé, G.; Cottone, S.
Abstract : Objective: Analyzing 25-hydroxyvitaminD (25[OH]D) serum levels and common carotid intima-media thickness (IMT) relationship, and evaluating the association of FokI and BsmI vitamin D receptor (VDR) gene polymorphisms with IMT in essential hypertensive patients were our study aims. Design and method: We enrolled seventy-one essential hypertensive patients, 18–75 years old. Patients underwent clinical blood pressure (BP) measurement, 24 hour ambulatory blood pressure monitoring, routine blood test, 25[OH]D assay and common carotid IMT evaluation. FokI and BsmI VDR polymorphisms were analyzed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: We did not find significant correlation between 25[OH]D and IMT. IMT was correlated with 24 h systolic BP, 24 h pulse BP, age, body mass index, glomerular filtration rate estimated by CKD-EPI equation, and HDL cholesterol in the univariate analysis, but not in the multivariate model. When we divided patients in accordance to FokI or BsmI VDR genotypes, there were not differences in IMT among the groups. No association between a specific genotype or allele and IMT greater than 0.9 mm was pointed out (Figure 2). Figure. No caption available. Conclusions: Our results seem to exclude any association between either 25[OH]D concentrations or VDR FokI and BmsI polymorphisms and common carotid IMT in essential hypertensive individuals.